An empirical study in assessing the impact of foreign workers on labour productivity in the Malaysian manufacturing sector - Tajuddin, Sheikh Ahmad Faiz Sheikh Ahmad; Halim, Mutia Sobihah Abd; Foziah, Nik Hazimi Mohammed; Zain, Fahru Azwa Mohd; Abdullah, Hamdy; Abidin, Ahmad Firdhauz Zainul (Asian Development Policy Review, 2023)
This study investigates the impact of foreign workers on labour productivity within the manufacturing industry of Malaysia. The study utilized panel data from 297 manufacturing firms registered with the Federation of Malaysian Manufacturers (FMM), covering the ten-year period from 2008 to 2017, and analysed it using static panel data regression to measure the effect of foreign workers on labour productivity. The findings of the study indicate that the employment of foreign workers, particularly those with low skills, has a negative impact on labour productivity. Low-skilled foreign workers often possess a restricted level of education and skills that may not be compatible with the demands of modern industries. Consequently, they may face challenges in adjusting to novel technologies, procedures, or intricate assignments, thereby impeding their overall productivity. It can be concluded that the employment of low-skilled foreign workers in Malaysia's manufacturing sector negatively affects labour productivity. The limited education and skills of these workers hinder their ability to adapt to new technologies and complex tasks, leading to diminished productivity levels. The findings are useful in highlighting to regulators, employers, and workers the effect of foreign workers on labour productivity. The study implies that necessary skills should be provided to low-skilled foreign workers. By enhancing their skills, these workers can better meet the demands of modern industries and contribute more effectively to the manufacturing sector in Malaysia.